Stability and boundedness results on certain nonlinear vector diferential equations of fourth order - Tunç, C. (Нелінійні коливання, 2006)
We consider the equation
X⁽⁴⁾ + Φ(X'')X''' + F(X, X')X'' + G(X') + H(X) = P(t, X, X', X'', X''')
in two cases: P ≡ 0 and P ≠ 0. In the case P ≡ 0, the asymptotic stability of the zero solution X = 0 of
the equation is investigated; in the case P ≠ 0 the boundedness of all solutions of the equation are proved. Розглядається рiвняння X⁽⁴⁾ + Φ(X'')X''' + F(X, X')X'' + G(X') + H(X) = P(t, X, X', X'', X''')
у двох випадках: P ≡ 0 та P ≠ 0. У випадку P ≡ 0 вивчається асимптотична стiйкiсть
нульового розв’язку X = 0 рiвняння; у випадку P ≠ 0 доведено обмеженiсть усiх розв’язкiв
рiвняння.